2007
DOI: 10.1111/j.1471-0528.2007.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective longitudinal population‐based study of clinical miscarriage in an urban Swedish population

Abstract: Objective To describe the incidence of clinical miscarriage and to investigate the factors influencing the occurrence of clinical miscarriage.Design Prospective study with both cross-sectional and longitudinal comparisons.Setting City of Göteborg, Sweden.Population Population-based study in cohorts of 19-year-old women followed longitudinally.Main outcome measures Incidence of miscarriage and pregnancy outcome. Results Complete data were available for 341 women born in 1962 and assessed up to the age of 39 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 30 publications
7
50
1
4
Order By: Relevance
“…Age is already recognized as one of the most important risk factors for miscarriage as shown in several previous studies (17)(18)(19), and in this study we found that age was the most significant predictor. However, the new finding in this study is that an increase in the BMI acts independent of age.…”
Section: Figuresupporting
confidence: 43%
“…Age is already recognized as one of the most important risk factors for miscarriage as shown in several previous studies (17)(18)(19), and in this study we found that age was the most significant predictor. However, the new finding in this study is that an increase in the BMI acts independent of age.…”
Section: Figuresupporting
confidence: 43%
“…10,11 Başarılı bir implantasyon için olmazsa olmaz faktörler reseptif bir endometriyum, canlı bir blastokist ve endometriyum ile blastokist arasındaki uyumlu iletişimdir.…”
Section: Erken Gebeli̇k Kaybiunclassified
“…Une FCS du 1 er trimestre complique 10 à 20 % des grossesses cliniques et concerne une femme sur quatre durant sa période d'activité génitale [4,5]. Première cause d'urgence en gynécologie, elle est le plus souvent vécue douloureusement par une patiente.…”
Section: Grossesses Non éVolutives Ou Fausses Couches Spontanées Du Punclassified